An introduction to the profession of social work : becoming a change agent - Elizabeth A. Segal; Karen E. Gerdes; Sue Steiner (Boston : Cengage Learning, Inc., 2019)
Provides a balanced introduction to the social work profession and helps students to understand the role it plays in the social welfare system. Updated throughout, the sixth edition integrates the core competencies and recommended practice behaviors outlined in the most recent Educational Policy and Accreditation Standards (EPAS) set by the Council on Social Work Education. -- Provided by publisher
1. What Is Social Work?2. The History of the Social Welfare System and the Social Work Profession.3. Poverty and Economic Disparity.4. Human Rights and Social and Economic Justice.5. Dimensions of Diversity.6. Generalist Social Work Practice.7. Child Welfare: Working with Children and Their Families.8. Gerontology: Working with People Who Are Older.9. Health Care Services.10. Mental Health Services.11. School Social Work.12. Substance Abuse.13. Violence, Victims, and Criminal Justice.14. Crisis, Trauma, and Disasters.Appendix A: NASW Code of Ethics.Glossary.
Keywords: Human services; Social problems & social services